2022
DOI: 10.1097/mat.0000000000001647
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Scaling of a Biomimetic Microfluidic Oxygenator

Abstract: Extracorporeal membrane oxygenation (ECMO) has been advancing rapidly due to a combination of rising rates of acute and chronic lung diseases as well as significant improvements in the safety and efficacy of this therapeutic modality. However, the complexity of the ECMO blood circuit, and challenges with regard to clotting and bleeding, remain as barriers to further expansion of the technology. Recent advances in microfluidic fabrication techniques, devices, and systems present an opportunity to develop new so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The highest blood flow rate for a microfluidic ECMO device prior to this work reported 5 vol% oxygen transfer at 240 mL min⁻ 1 using an 8‐layer device [ 52 ] based on a previously reported design, [ 57 ] but this device exhibited high blood pressure drop and was not tested in an animal model. The highest blood flow rate in a microfluidic oxygenator tested in an animal model was reported by Dabaghi et al., where devices achieved 95% oxygen saturation at a flow rate under 100 mL min⁻ 1 in a 16‐layer stack, [ 35 ] a configuration that would require 167 layers to reach a neonatal oxygenator scale (a comparison of the performance metrics from two recent animal studies using microfluidic oxygenators with those from the current study is summarized in Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest blood flow rate for a microfluidic ECMO device prior to this work reported 5 vol% oxygen transfer at 240 mL min⁻ 1 using an 8‐layer device [ 52 ] based on a previously reported design, [ 57 ] but this device exhibited high blood pressure drop and was not tested in an animal model. The highest blood flow rate in a microfluidic oxygenator tested in an animal model was reported by Dabaghi et al., where devices achieved 95% oxygen saturation at a flow rate under 100 mL min⁻ 1 in a 16‐layer stack, [ 35 ] a configuration that would require 167 layers to reach a neonatal oxygenator scale (a comparison of the performance metrics from two recent animal studies using microfluidic oxygenators with those from the current study is summarized in Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COMSOL model was set up as described in Supporting Information 2. Using data from previous iterations of devices [45,52,57] with varying thickness membranes and back pressures, the model was tuned to precisely match the device performance by adjusting the membrane permeability and using an apparent oxygen diffusivity and solubility in blood (as opposed to using literature values, see Supporting Information 2 for details). Because devices were tested that had different channel heights (65 μm vs 200 μm), lengths (4.7 and 8 cm), and various measured membrane thicknesses (50-100 μm), and were tested at different back pressures, the oxygen diffusivity and solubility of both the membrane and the blood could be independently back-calculated to create a model that precisely matched the data from all testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter approach would eliminate the non‐physiologic forces that damage red blood cells and platelets and ultimately trigger abnormal coagulation and inflammatory responses in the circuit and patient. Recent advances in the field of microfluidics have led to the design, fabrication, and testing of “artificial lung” membranes with very high gas permeability, in which blood flows through a network of bio‐inspired capillary microchannels 27–32 . The purpose of this review is to summarize the progress that has been made in the design, development, and scaling of these membranes with a specific focus on the capability of this approach to improve the bio−/hemo‐compatibility and clinical outcomes of current and future ECMO devices.…”
Section: Introductionmentioning
confidence: 99%
“…To date, our and other research groups have demonstrated small-scale, single-layer two-dimensional (2D) µALs with record gas exchange efficiency [10,11], biomimetic blood flow networks [10][11][12][13][14][15][16][17][18], surface coatings to reduce protein and platelet deposition and increase lifetime [15,[19][20][21][22], and have also shown that endothelial cells can be grown in microfluidic blood flow networks and significantly reduce thrombus area [16,[23][24][25]. Manufacturing techniques have been demonstrated to increase the blood flow capacity of µAls and move these devices towards clinical application [11,14,16,[26][27][28][29][30][31][32]. These previous µALs have been designed with small artificial capillary diameters (10-40 µm) to maximize gas exchange efficiency or with larger diameters (~100 µm) to simplify construction and potentially minimize clotting.…”
Section: Introductionmentioning
confidence: 99%